Предмет: Алгебра,
автор: Анонимус57
упростите выражение
(√6-√2)в квадрате*(8+2√12)
Ответы
Автор ответа:
0
(V6 -V2)^2 * (8+2V12) = (6-2V6V2+2)*(8+2V12) = (8-2V12)*(8+2V12) = 8^2 - (2V12)^2 =
64 - 4*12 = 16
Автор ответа:
0
(√6-√2)² *(8+2√12)
раскрываем скобки: √6² - 2√12+ √2² * 8+2√12
-2√12 и 2√12 сокращаются, остается
6+2*8=22
Ответ:22
Похожие вопросы
Предмет: Русский язык,
автор: dingulovaasilay
Предмет: История,
автор: arder36
Предмет: География,
автор: Аноним
Предмет: Литература,
автор: юляшка232